The Influence of Teachers’ Expectation and Principal’s Supportive Supervision on Teachers’ Performance - Rofiq Faudy Akbar (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2020)
The study aimed to explain the teachers’ expectations and the principal’s supportive supervision on the teachers’ performance. It was also to reveal the mediation of supportive supervision variables between job expectation and teachers’ performance. The respondents included the private madrasa teachers in Kudus, Demak, and Jepara. The research produced several findings. First, madrasa teachers have an expectation regarding their job. The indicators included expectations for career opportunities (becoming a permanent employee/obtaining a permanent position, certification) and that madrasa will take some efforts to increase their well-being. Second, according to the teachers, the principal's supportive supervision included listening to the subordinates’ problems, motivating the subordinates, and providing positive feedback. Third, the measurement results indicated that expectation and supportive supervision influenced the teachers’ performance by 30%. Meanwhile, the rest 70% was by other variables outside the model used in the research. Fourth, the expectation has a significant effect on teacher performance through supervision support variables in the t-statistic 2.732 with a significance of 5%. The supportive supervision variable can mediate the relationship between expectation and teacher performance expectation significantly affected the teachers’ performance through supportive supervision with t-statistics score of 2,732 and 5% significance. Supportive supervision mediated the relation between expectation and teachers’ performance.